THE EFFECT OF AL-MA’TSURAT MORNING-EVENING RECITATION ON PHYSIOLOGICAL RESPONSE TO ANXIETY LEVEL IN ICU PATIENTS - Moch. Achwandi; Khusniyah, Zulfa (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
ICU patients often experience anxiety due to critical conditions, unfamiliar environments, and invasive medical procedures. Anxiety can lead to physiological changes such as increased blood pressure, heart rate, and respiratory rate. This study aimed to analyze the effect of the Al-Ma’tsurat morning-evening recitation on the physiological response to anxiety in ICU patients. A pre-experimental design with a pretest-posttest approach without a control group was used. The sample consisted of 42 ICU patients at RSI Sakinah Mojokerto who met the inclusion criteria, selected through purposive sampling. Data were collected by measuring blood pressure, heart rate, and respiratory rate before and after the intervention. Paired t-test and Wilcoxon test results showed no significant difference in systolic and diastolic blood pressure or heart rate (p > 0.05). However, a significant difference was found in respiratory rate (p = 0.015) after listening to the Al-Ma’tsurat recitation. The reduction in respiratory rate indicates a physiological relaxation response due to spiritual intervention. Although most parameters were not statistically significant, dzikir therapy remains potentially effective as a non-pharmacological holistic intervention for ICU patients.